Impact of heat waves on cardiovascular and respiratory morbidity and mortality in municipalities of Northeast Brazil (Sustainability in Debate, 2022)
In recent years, a vast number of studies have been generated on the impacts caused by heat waves on the health of the population. This study analyzes how heat waves that occur between the months of October and March increase the risks of morbidity and mortality of the population of five northeastern municipalities: Belém de São Francisco, Floresta, Itacuruba, Jeremoabo, Paulo Afonso and Petrolândia. It is observed that the months of January, February and October are the ones that present the most cases of morbidity and mortality of the population and that the municipality of Belén do São Francisco presents the greatest probability of risk. A consistent positive signal was found between heat waves and cardiovascular hospitalization. We also observe an increase in temperatures in the region during the last 30 years, as evidence of a possible future risk.